IMPROVEMENT THE WORKS OF FREIGHT FORWARDING SERVICE AT KHARKOV-LISKI STATION - Кравченко, Сергій Валентинович; Продащук, Світлана Миколаївна (Eastern-European Journal of Enterprise Technologies, 2010)
The analysis of the main lacks of forwarding services was made. The measures for improvement of the station: the introduction of universal quality management (TQM), which significantly help streamline the processes of work organization were proposed.